PENGARUH STRUKTUR KEPEMILIKAN TERHADAP KUALITAS AUDIT DENGAN VARIABEL MODERASI IMBALAN AUDIT - Sumantaningrum, Yohana Lalitya; Kiswara, Endang (Diponegoro Journal of Accounting, 2017)
The purpose of this study is to examine the effect of ownership structure on audit quality proxied with accrual quality and analyze the role of audit fees proxied with abnormal audit fee as a moderator in the relationship influence the ownership structure of the quality of audit. Independent variabels that used in this research is ownership structure as measured by institutional ownership, managerial ownership and foreign ownership, while the dependent variable is audit quality proxied with audit quality. The population use in this study are all non-financial companies listed in Indonesia Stock Exchange year 2013-2014. The sample of research is a non-financial company listed on the Indonesia Stock Exchange 2013-2014 reporting audit fee. The sample of this study consisted of 86 total samples and 443 total observations from the annual report. Based on the Partial Least Square were perfomed to produce that institutional ownership and foreign ownership have a positive influence but not a significant influence on audit quality proxied with accrual quality. Meanwhile, managerial ownership has negative influence, but not a significant influence on audit quality proxied with accrual quality. Moderating variables audit fee is only able to moderate the relationship of foreign ownership on audit quality. While the relationship between institutional ownership to audit quality and managerial ownership to audit quality was not able to be moderated by audit fees.